2020
DOI: 10.1002/elps.201900428
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and high‐performance immobilized enzyme reactor: DNA‐directed immobilization of multienzyme in polyamidoamine dendrimer‐functionalized capillaries

Abstract: In recent years, CE‐integrated immobilized enzyme reactors (IMERs) for single‐enzyme immobilization have attracted considerable attention. However, there has been little research on multienzyme immobilization in CE. Here, we introduce a method for fabricating a CE‐integrated IMER, using DNA‐directed immobilization to fix glucose oxidase and horseradish peroxidase in the capillary, which had been functionalized with polyamidoamine dendrimer (PAMAM). Owing to the reversibility of DNA hybridization, the reactor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In line with previous work performed in 2013 [86], this time frame also witnessed the simultaneous analysis of two enzymes in one run either offline [61,87] or inline [53,77,80].…”
Section: Discussionsupporting
confidence: 81%
“…In line with previous work performed in 2013 [86], this time frame also witnessed the simultaneous analysis of two enzymes in one run either offline [61,87] or inline [53,77,80].…”
Section: Discussionsupporting
confidence: 81%
“…Other than spherical nanoparticles, surfaces of other shapes may also be used for immobilizing DNA-guided multienzyme systems to adapt different application scenarios. For example, Li et al built a capillary electrophoresis-integrated immobilized enzyme reactor (CE-IMER), in which the ssDNA strands for directing the immobilization of complementary ssDNA-coupled GOx and HRP were fixed on the inner surface of a capillary (Figure 4B,E) (Li et al, 2020).…”
Section: Multi-enzyme Systems Constructed Based On Simple Dna Scaffoldsmentioning
confidence: 99%
“…Using them as carriers to directionally coimmobilize multiple enzymes has shown great potential for the precise positioning of enzyme molecules. [10,22,23] Many kinds of literature have reported that various DNA assemblies constructed by DNA origami can accurately position multiple enzymes. [24,25,26] Recently, a DNA tetrahedral scaffold [27] as well as a switchable trident-shaped DNA nanoactuator [28] has been prepared to co-immobilize GOD and HRP.…”
Section: Introductionmentioning
confidence: 99%